About the structure of finite groups, whose all non-Abelian subgroups are subnormal - Kurdachenko, L. A.; Semko, M. M.; Atlihan, S. (Reports of the National Academy of Sciences of Ukraine, 2014)
We study infinite groups, all non-Abelian subgroups of which are subnormal. Some results of these groups' structure and the full description of locally finite groups having a specified property are given.